Advances in pathophysiological mechanisms and therapeutic efficacy of exercise rehabilitation in patients with heart failure with preserved ejection fraction - Fang, Juanjuan; Wang, Zhenhua; Yu, Jiangshui (Frontiers in Cardiovascular Medicine, 2025)
Heart Failure with Preserved Ejection Fraction (HFpEF) is a heterogeneous syndrome characterized by systemic multiorgan dysfunction, and exercise rehabilitation has emerged as a promising non-pharmacological intervention. This review synthesizes current evidence on the pathophysiological mechanisms underlying exercise intolerance in HFpEF and evaluates the therapeutic efficacy of exercise-based interventions. Key mechanisms include myocardial stiffness due to chronic inflammation, coronary microvascular dysfunction, skeletal muscle mitochondrial impairment, and endothelial dysfunction. Clinical studies indicate that tailored exercise regimens (e.g., combined aerobic-resistance training) improve peak oxygen consumption, 6 min walking distance, and quality of life through multi-organ adaptations: enhanced cardiac output reserve, skeletal muscle metabolic remodeling, and reduced systemic inflammation. However, challenges persist in optimizing exercise prescriptions for phenotypically diverse HFpEF subpopulations (e.g., obese, elderly frail). Future research must prioritize phenotype-specific protocols, validate long-term outcomes (mortality, hospitalization), and integrate biomarkers (e.g., H2FPEF score) with digital health technologies to advance precision rehabilitation strategies. This review highlights the imperative for mechanistic insights to guide clinical translation in HFpEF management.